Students Awareness of Green Consumer Behaviour and Sustainable Environment in Ghana: Using OpenBugs - Keelson, Solomon Abekah; Johnson, Joseph Ahinful (Journal of Management Research, 2024)
Green marketing has been widely studied because of its importance in marketing theory. The purpose of this green marketing study unlike previous ones was to examine student’s awareness of how their green consumer behaviour impact environmental sustainability. A total of three hundred and seventeen (317) tertiary students from the Technical Universities of Ghana were used as respondents in a simple random sampling approach, using the internet survey method. Using the OpenBUGS Bayesian statistical technique, the findings of the present study showed an average level of awareness of green products; students consider the potential environmental impact of their actions when making purchase decisions, and as their purchase habits are affected by their concern for the environment. Thus, students are able to distinguish between green product and non–green product. Again, they know the benefits of green products, and would prefer buying green product as first option. Moreover, they believe green buying behavior can contribute to saving the environment because the study showed a direct relationship between buying behavior and the environmental concerns. Finally, the ANOVA results revealed that male students’ response to green product is positive compared to their female counterparts, whose response to green product are negative. The study recommended that institutions could include in their marketing curricula subjects that train students on consumer knowledge, awareness, values, attitudes, expectations, perceptions and concerns for the environment.